2016
DOI: 10.1039/c6em00256k
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation in the toxicity of graphene oxide nanosheets towards Escherichia coli in the presence of humic acid

Abstract: GO nanosheets have been reported to show strong cytotoxicity towards Escherichia coli (E. coli) in aqueous solution. Natural organic matters (NOMs) in water may probably coat on the surface of GO nanosheets, which possibly influence its cytotoxicity. In this study, we illustrated how humic acid (HA), a ubiquitous NOM, mitigated the toxicity of GO nanosheets towards E. coli based on the cytotoxicity mechanism of GO nanosheets. Adsorption and cell viability tests proved that HA was adsorbed by GO nanosheets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…As for the graphene oxide, Zucker et al reported that the extent of membrane damage depended on the total surface area of graphene oxide (Zucker et al 2017). Normally, an eco-corona could hinder the physical contact between graphene and cell membranes through steric hindrance or electrostatic repulsion, which could reduce membrane damage (Zhang et al 2016;Zhao et al 2019). For invertebrate animals or zebrafish larvae, a few studies reported that HA could significantly increase the toxicity of graphene to organisms by enhancing its stability (Castro et al 2018;Clemente et al 2017).…”
Section: Mechanisms By Which Nom Influences the Toxicity Of Nms By Aq...mentioning
confidence: 99%
“…As for the graphene oxide, Zucker et al reported that the extent of membrane damage depended on the total surface area of graphene oxide (Zucker et al 2017). Normally, an eco-corona could hinder the physical contact between graphene and cell membranes through steric hindrance or electrostatic repulsion, which could reduce membrane damage (Zhang et al 2016;Zhao et al 2019). For invertebrate animals or zebrafish larvae, a few studies reported that HA could significantly increase the toxicity of graphene to organisms by enhancing its stability (Castro et al 2018;Clemente et al 2017).…”
Section: Mechanisms By Which Nom Influences the Toxicity Of Nms By Aq...mentioning
confidence: 99%
“…Humic acid (HA), the main existing form of NOMs (natural organic matters), can interact extensively with various engineered nanoparticles to improve their stability in aqueous solutions (Pradhan et al 2018). The potential contamination of a river or lake by NM can be mitigated by an abundancy of HA (Kteeba et al 2017) since it contains many hydrophilic groups that show excellent ability to adjust the behaviors and toxicities of NM in the environment (Zhang et al 2016). Indeed, some studies have shown that the presence of HA in the exposure medium alters the toxicity of the NMs (Dasari and Hwang 2013;Deng et al 2016;Hu et al 2011;Kim et al 2013;Yang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Humic acid as a natural organic matter has been found to be an effective graphene oxide toxicity alleviation agent in E. coli aqueous bacterial model. This natural agent exhibited an antioxidant action role, maintaining the activity of the antioxidant enzymes and decreasing the reactive oxygen species generation, as witnessed by the results of oxidative stress experiments, thereby having important ecotoxicology implications [120].…”
Section: Other Exploitable Environmental and Biological Factorsmentioning
confidence: 95%